2015
DOI: 10.1371/journal.pone.0135767
|View full text |Cite|
|
Sign up to set email alerts
|

Japanese Encephalitis in Assam, India: Need to Increase Healthcare Workers’ Understanding to Improve Health Care

Abstract: IntroductionJapanese encephalitis (JE) is a major cause of high morbidity and mortality in several states across India. However, in 2014, a sharp rise was observed in the number of cases of JE in north-eastern Assam state, and 51% of the total cases of JE in India were reported from the Assam in the same year. In this regard, a study was conducted to evaluate the knowledge and attitudes of healthcare workers in Darrang, a district of Assam highly affected by JE.MethodsA cross sectional study was conducted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
5
11
0
Order By: Relevance
“…[3,5] Children under age of 15 years are major victim of JE. [6] Studies showed that in JE endemic area, nearly all cases occur in children <10 years of age. Those who survived, majority of them followed by some sort of morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[3,5] Children under age of 15 years are major victim of JE. [6] Studies showed that in JE endemic area, nearly all cases occur in children <10 years of age. Those who survived, majority of them followed by some sort of morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Those who survived, majority of them followed by some sort of morbidity. [6,7] JE infections are mostly asymptomatic. 1 in 300 infections is symptomatic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30][31][32][33][34][35][36][37][38] There is also a need to increase health workers' understanding on Ebola disease to improve healthcare like any other viral disease. [39] …”
Section: Drug and Vaccine Developmentmentioning
confidence: 99%